YIELD AND CHANGES IN THE FRUIT QUALITY OF CHERRY TOMATO GROWN ON THE COCOFIBRE AND ROCKWOOL SLABS USED FOR THE SECOND TIME - Aliaksandr Abukhovich; Jolanta Kobryń (Acta Scientiarum Polonorum: Hortorum Cultus, 2010)
Greenhouse cultivation of four cultivars of cherry tomato (Goldita, Faworita, Flavorino, Organza) on the substrates used for the second time (cocofibre and rockwool) did not show any differences in their yielding. Fruits obtained from cultivation on the cocofibre contained less dry matter and vitamin C. During the vegetation period some changes in fruit quality were observed. In the first weeks of fruiting more organic acids and less of vitamin C were observed in fruits. At the time of full fruiting (II period) the content of vitamin C was at its highest and at the same time the content of organic acids and dry matter at the lowest. At the end of vegetation (III period) fruits contained more dry matter and total sugars). Cultivars significantly differed in respect to yielding and fruit quality. The highest content of the investigated components was characteristic for Favorita and Goldita cultivars and the lowest for Organza. However, that cultivar produced the highest total and marketable yield.